PCDH10 promoter hypermethylation is frequent in most histologic subtypes of mature lymphoid malignancies and occurs early in lymphomagenesis. Issue 11 (9th August 2013) - Narayan, Gopeshwar; Xie, Dongxu; Freddy, Allen J.; Ishdorj, Ganchimeg; Do, Catherine; Satwani, Prakash; Liyanage, Hema; Clark, Lorraine; Kisselev, Sergey; Nandula, Subhadra V.; Scotto, Luigi; Alobeid, Bachir; et al.
<x xml:space="preserve">Abstract</x> PCDH10 is epigenetically inactivated in multiple tumor types; however, studies in mature lymphoid malignancies are limited. Here, we have investigated the presence of promoter hypermethylation of the PCDH10 gene in a large cohort of well‐characterized subsets of lymphomas. PCDH10 promoter hypermethylation was identified by methylation‐specific PCR in 57 to 100% of both primary B‐ and T‐cell lymphoma specimens and cell lines. These findings were further validated by Sequenom Mass‐array analysis. Promoter hypermethylation was also identified in 28.6% cases of reactive follicular hyperplasia, more commonly occurring in states of immune deregulation and associated with rare presence of clonal karyotypic aberrations, suggesting that PCDH10 methylation occurs early in lymphomagenesis. PCDH10 expression was down regulated via promoter hypermethylation in T‐ and B‐cell lymphoma cell lines. The transcriptional down‐regulation resulting from PCDH10 methylation could be restored by pharmacologic inhibition of DNA methyltransferases in cell lines. Both T‐ and B‐cell lymphoma cell lines harboring methylation‐mediated inactivation of PCDH10 were resistant to doxorubicin treatment, suggesting that hypermethylation of this gene might contribute to chemotherapy response. © 2013 Wiley Periodicals, Inc.